Pengaruh Adversity Quotient dan Learning Organization terhadap Kinerja Pegawai Pusdiklat Kemensetneg RI - Hermawan Setiaji; Anik Herminingsih (Universitas Negeri Surabaya, 2018)
The progress of the reformation in the field of bureucracy is slower than the other fields. It is believed that the concept of the clean government and good governance must be applied in order to give the optimal results for the citizen. In this case, the quality or work of those who worked in the bureaucracy of the State Secretariat Training Center of the Republic of Indonesia did not show any optimal results. As a matter of fact, there were several factors that contributed to the results, for instances adversity quotient and learning organization. Furthermore, this research aimed to determine the effect of adversity quotienent and learning organization of employee performance. The research was conducted at the Training and Education Centre State Secretary of The Republic of Indonesia in Jakarta. Research design that used is causality, with descriptif quantitative analysis, using instrument questionnaire to population sample. The result showed that: (1) there is a positive correlation and significant effect of adversity quotient on the performance of employee; (2) there is a a positive correlation and significant effect of learning organization on the performance of employee; (3) and these is a positive and significant effect simultanuoesly adversity quotient and learning organization on the performance of employee.